Migrations féminines et reconfigurations familiales autour des enfants left behind en Bolivie - Robin Cavagnoud (Les Cahiers ALHIM)
Given precariousness of labor market in Bolivian Altiplano towns, particularly in El Alto, many women choose to migrate alone, mainly to Argentina and Spain, to give their children better living conditions in the country of origin. Firstly, the article shows the organization of these mothers’ migration in their female kin. Secondly, it analyzes the use of remittances sent by women for the daily needs of their children and their own long-term projects. Finally, it deals with the children’s care by female members of migrant women family bloodline and the left behind children autonomy process according to marital and reproductive status of their mother in the country of destination.